2008
DOI: 10.1007/s00026-008-0347-0
|View full text |Cite
|
Sign up to set email alerts
|

Planar Triangulations with Real Chromatic Roots Arbitrarily Close to 4

Abstract: We exhibit infinite families of planar triangulations with real chromatic roots arbitrarily close to 4, thus resolving a long-standing conjecture in the affirmative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 19 publications
2
32
0
1
Order By: Relevance
“…And one might hope that a method which improves Conjecture 1 for k ≥ 5 might also be applicable for the interval from 4 to 5. In contrast to this, Royle [6] has shown that planar graphs have chromatic real root arbitrarily close to 4.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…And one might hope that a method which improves Conjecture 1 for k ≥ 5 might also be applicable for the interval from 4 to 5. In contrast to this, Royle [6] has shown that planar graphs have chromatic real root arbitrarily close to 4.…”
Section: Introductionmentioning
confidence: 95%
“…However, if G has no separating triangles we can improve the inequality (8), since none of the polynomials in equations (5), (6) are the zero polynomial. More precisely,…”
Section: The Chromatic Polynomialmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobsen et al [7] extended this to show that B 7 , B 8 , B 9 and B 10 are likewise accumulation points of real chromatic roots of plane triangulations (namely, m per × n free pieces of the triangular lattice of width m up to 12). Finally, Royle [9] has recently exhibited a family of plane triangulations with chromatic roots converging to 4. We know that the sequence B n has a limit 4.…”
Section: Some Questions and Remarksmentioning
confidence: 99%
“…If the answer to Beraha's question is positive, then there exist planar graphs whose chromatic roots are arbitrarily close to 4. Note that by exhibition of Royle [9], we have a family of plane triangulations with chromatic roots converging to 4. Of course, it is an open question which other numbers in the interval (32/27, 4) can be accumulation points of real chromatic roots of planar graphs.…”
Section: Some Questions and Remarksmentioning
confidence: 99%